ANALISIS KOMUNIKASI PENDIDIK TERHADAP SISWA BERKEBUTUHAN KHUSUS DI SEKOLAH LUAR BIASA (SLB) SURAKARTA - Hapsari, Lintang Ayu; Ramadhani, Nabila Oktavia; Fauzy, Ibrahim; Minsih, Minsih (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This research aims to analyze the communication patterns and characteristics used by educators towards students with special needs at SLB Surakarta. Effective communication between educators and students is essential in the learning process, especially in special education settings, where students have a wide range of different needs and abilities. This research uses a qualitative method with a phenomenological approach, which allows researchers to explore direct and in-depth experiences regarding communication interactions between educators and students. Data collection techniques used include observation, interviews, literature study, and information analysis. The results of the research show that there are several communication patterns used by educators at SLB C1 YSSD Surakarta in interacting with students with special needs, including: (1) Two-way communication patterns that encourage active interaction between teachers and students, (2) Verbal communication patterns that involves the use of simple and easy to understand language, (3) Nonverbal communication patterns which include facial expressions, body movements, and gestures to support the message conveyed, (4) Repeated communication patterns carried out to ensure student understanding, (5) Communication patterns that emphasize each word to attract students' attention and help them stay focused, and (6) Communicate with empathy and openness to build closer relationships and support the learning process. The conclusion of this research shows that educators at SLB Surakarta apply various communication patterns designed to overcome challenges in interacting with students with special needs, by emphasizing the importance of clear, empathetic and open communication to support successful learning